Accounting training research at universities of Tunja - Molina-Hurtado, Yudy Alexandra; Fonseca-Gordillo, José Eustacio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
In the years 2010 to 2015, a study on formative research in public accounting programs of higher education institutions in the city of Tunja, Colombia, was made. The research assumes the qualitative and descriptive approach. The results show that the training of public accountants in Tunja, is framed in areas such as auditing, finances, taxation, international financial reporting standards and costs. The predominant tendencies are auditing and finance, reflecting the articulation with the global economic policies that over time have led the way within the construction of curriculum, guaranteeing updated and quality training processes. In the same way, the research process represents a low percentage in relation to the other options to choose a professional degree, such as internships and specialization or master's courses related to the field of study. In conclusion, there is still a long way to go in the field of formative accounting research, so that proposals are generated to strengthen its praxis in the area of influence of the universities.